Dogodek v poeziji Maje Vidmar, Alojza Ihana in Uroša Zupana - Ocepek, Manja (Slavistična revija, 2025)
This article adresses the question of the presence of events in lyric poetry. It introduces recent theoretical approaches to this category and applies them to the works of the most prominent members of the generation of poets born around 1960 – Maja Vidmar, Alojz Ihan, and Uroš Zupan. Their poetics are frequently associated with the notion of narrativity, a concept linked to the broader discussion of the narrative turn in contemporary (Slovenian) poetry. All three demonstrate an interest in narrative strategies, particularly an event and its associated story. However, despite narrativization, their poetry – due to the role attributed to the events presented – remains fundamentally lyrical. The analysis highlights narrativity as a shared feature of an otherwise heterogeneous, syncretic Slovenian poetry, characterized by a pluralism of autopoetics as it enters the new millennium.
Keywords: contemporary Slovene lyric poetry; Ihan, Alojz; lirsko-epska hibridnost; lyric-narrative hybridity; narativnost; narrativity; Slovene literature; slovenska književnost; sodobna slovenska poezija; teorija lirike; theory of the lyric; Vidmar, Maja; Zupan, Uroš